The cultivation of opinions. How did the press cover the last 16 years of experience with GMOs in Canada? - Eleni A. Galata (Cogent Business & Management, 2017)
The media debate on agricultural biotechnology (ag-biotech) in Canada engages active supporters and opponents. At the same time, Canadian citizens are found to be polarized with regard to Genetically Modified Organisms (GMOs). Studies suggest that this is partly a result of the biased coverage of the media. I used two widely read national newspapers and examined their stories on GMOs from the years 2000 to 2015. First, I examined whether the stories were biased in evaluations towards GMOs and I then looked at the dynamics of this bias. My results suggest that the press coverage on GMOs in Canada is not biased since representatives from both sides of the debate were found in the press. However, one might see this as an “artificial balance” because the representatives themselves were found to express opinions that could be characterized as biased. I conclude that the press exposure can have a cultivation effect, letting the public reflect what they find in press instead of the real world, and leading to polarized public perceptions on GMOs. This work presents the first effort to understand the levels of media bias that leads to public polarization on ag-biotech. The results add to the literature of public understanding of the media by presenting the ways in which the representatives of the media can express opinions that are biased.
Keywords: 650